1992
DOI: 10.1111/j.1365-2605.1992.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm nuclear instability and staining with aniline blue: abnormal persistance of histones in spermatozoa in infertile men

Abstract: During mammalian spermiogenesis, replacement of the somatic histones by basic proteins, the protamines, allows normal sperm nuclear condensation. In this study we have evaluated the degree of chromatin compaction in spermatozoa from 191 infertile subjects, affected by different testicular disorders, compare with that in 50 fertile sperm donors (controls). In infertile men, there was a higher percentage of unstable spermatozoa after incubation with sodium dodecyl sulphate (SDS) and of stained spermatozoa after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 17 publications
3
64
0
3
Order By: Relevance
“…When we compared the morphology and CMA 3 fluorescence in individual spermatozoa, we found a high frequency of CMA 3 positive nuclei among macrocephalic spermatozoa in both treatment groups. This confirms data known on other fluorescent dyes, in particular Acridine Orange, where access to the DNA was achieved only or mostly in cases of decondensed or damaged chromatin (Evenson et al, 1980;1991;Foresta et al, 1992;Molina et al, 1995;Sailer et al, 1995). Our observations also confirm that macrocephaly is associated with decondensation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…When we compared the morphology and CMA 3 fluorescence in individual spermatozoa, we found a high frequency of CMA 3 positive nuclei among macrocephalic spermatozoa in both treatment groups. This confirms data known on other fluorescent dyes, in particular Acridine Orange, where access to the DNA was achieved only or mostly in cases of decondensed or damaged chromatin (Evenson et al, 1980;1991;Foresta et al, 1992;Molina et al, 1995;Sailer et al, 1995). Our observations also confirm that macrocephaly is associated with decondensation.…”
Section: Discussionsupporting
confidence: 74%
“…A number of studies have shown that spermatozoa with abnormal nuclear chromatin organization are more frequent in infertile men than in fertile men (Evenson et al, 1980;Monaco and Rasch, 1982;Foresta et al, 1992). In these studies, specific dyes and fluorochromes were used to assess the chromatin of mature mammalian spermatozoa and relate them to fertilization results.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, it must be remembered that several studies have demonstrated that a variable but consistent fraction of human spermatozoa exhibits abnormalities in chromatin structure, not always detected using classical parameters of evaluation (12)(13)(14)(15)(16)(17)(18)(33)(34)(35). Moreover the existence of a close relationship between chromatin and DNA structural abnormalities and male infertility has been well pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the Asian elephant, a terrestrial endorchid, it has been aniline blue, which is taken up by the abundant lysine residues present in the histones. A 595 significant association between defective abnormal sperm chromatin protamination and male subfertility has been reported [71][72][73]. Relationship between chromatin stability, protamination and fertility would provide fundamental information on chromatin status, which is expected to have a strong prognostic value on sperm function [39,74].…”
Section: Dolphin Spermatozoa Are Able To Fertilize Cow and Murine Oocmentioning
confidence: 99%